The mobility of the superficial and deep midfacial fat compartments: An ultrasound‐based investigation. (8th August 2021) - Schelke, Leonie; Velthuis, Peter J.; Lowry, Natalia; Rohrich, Rod J.; Swift, Arthur; Gotkin, Robert H.; Moellhoff, Nicholas; Frank, Konstantin; Dumbrava, Mihai; Cotofana, Sebastian
Abstract: Background: Understanding the mobility of the midface and the separate contributions of the superficial and deep fat compartments is essential for natural esthetic outcomes following soft tissue filler or fat grafting procedures. A study was designed that used ultrasound imaging to demonstrate in vivo visualization and quantification of distances and movements in the midface. Methods: A total of 48 midfaces of 24 healthy Caucasian volunteers, all naïve of esthetic procedures, (22 females; 46.85 (9.8) years; 22.83 (3.1) kg/m 2 ) were scanned using 18 MHz ultrasound imaging. Distances between bony landmarks (inferior orbital rim, infraorbital foramen) were used as markers to measure the cranial movement of the superficial (superficial nasolabial and superficial medial cheek fat compartment) and the deep (deep pyriform space, deep medial check fat compartment, deep lateral cheek fat compartment) midfacial fat compartments between resting and smiling facial position. Results: The superficial midfacial fat compartment moved, on average, 3.7 mm ( p  < 0.001) cranially, whereas the deep midfacial fat compartments moved, on average, 0.1 mm ( p  > 0.05) during smiling. No gender differences in mobility were identified ( p  > 0.05). Conclusion: The results obtained are in line with previous cadaveric investigations and revealed, in a highly statistically significant fashion, that the superficial midfacial fat compartments move in cranial direction whereas the deep fat compartment did not display similar positional changes. These results help to guide facial injectable treatments and to understand why, in the midface, a deep supraperiosteal approach should be favored when augmenting the deep midfacial fat compartments.